Visual Sociology Sociology 282A - Grady, John (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
On any given day we learn about the world through visual representation (images) of that world. Newspapers and journals re full of graphs, maps, photographs and advertisements. Television , which most of us now watch at least three or four hours a day, inundates us with a panoply of visual experience and explicit messages. Film, whether seen in theaters or at home ona VCR, still provides us with the signal art form of our times. Teachers and scientists increasingly communicate with even more compelling and dazzling displays of computer generated information that invites interaction participation. Finally, video recorders, computers and associated technologies now make it possible for professionals and others to produce and recycle preexisting images in most of their professional activities.